2004
DOI: 10.1016/j.engstruct.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of two-way reinforced concrete slabs in fire

Abstract: This paper describes numerical modelling of the fire behaviour of two-way reinforced concrete slabs using a special purpose non-linear finite-element program, SAFIR. Several two-way reinforced concrete and composite steel-concrete slabs are tested under exposure to the ISO standard fire in order to validate the shell finite element in the SAFIR program. The modelling results showed agreement with the fire tests and demonstrate that the SAFIR shell element can be used to predict tensile membrane behaviour of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 9 publications
1
44
0
1
Order By: Relevance
“…The program was developed for analysing steel or composite structures, but the shell element in SAFIR has been proven to also accurately predict the fire behaviour of RC slabs [13]. A previous study showed that SAFIR can successfully predict the structural behaviour of hibond slabs (proprietary composite slabs) using a combination of shell and beam elements [14], which is the basic idea behind the proposed model in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The program was developed for analysing steel or composite structures, but the shell element in SAFIR has been proven to also accurately predict the fire behaviour of RC slabs [13]. A previous study showed that SAFIR can successfully predict the structural behaviour of hibond slabs (proprietary composite slabs) using a combination of shell and beam elements [14], which is the basic idea behind the proposed model in this study.…”
Section: Introductionmentioning
confidence: 99%
“…SAFIR has been used extensively to simulate the fire behaviour of reinforced concrete slabs and its applicability has been verified experimentally [20]. The layers of reinforcing bars in the slab are treated as being smeared across the shell element and show uniaxial behaviour.…”
Section: Materials Properties and Modellingmentioning
confidence: 99%
“…This can possibly be attributed to a reasonably thick slab behaving in compressive membrane action. In recent years a number of numerical models have been developed for modelling the behaviour of reinforced concrete slabs in fire [4][5][6][7], but none of these have taken spalling into account.…”
Section: Introductionmentioning
confidence: 99%